Fatores de risco para a incidência de lesões de cárie em crianças e indicações para o uso de selantes em primeiros molares permanentes. - Emmanuelli, Bruno (2019)
The development of carious lesions in first permanent molars has been studied for a long time. Although the role of individual and contextual determinants on oral health is recognized, when considering the determinants and distal risk factors for dental caries incidence in first permanent molars the studies are still inconclusive. The aim of this cohort study was to evaluate the impact of individual and contextual factors of early childhood on the incidence of dental caries in first permanent molars. In addition, it was aimed to identify, by means of prediction values, the characteristics that could be used as a parameter for the indication of sealants in the first permanent molars. This seven-year follow-up study was conducted with 639 children aged 1 to 5 years who were initially assessed in a survey conducted in 2010. Dental caries was assessed by the International Caries Detection Assessment System (ICDAS) at baseline and follow-up. Contextual and individual variables were collected at the beginning of the study and included the presence of community cultural centers in the neighborhood where the child lived and demographic, socioeconomic, psychosocial and biological characteristics. In manuscript 1, a multi-level Poisson regression model was used to investigate the impact of individual and contextual characteristics on the dental caries incidence in first permanent molars. With this approach it was possible to estimate the incidence rate ratio (IRR) and the 95% confidence intervals (95% CI). From total children evaluated at the baseline, 449 were reassessed after seven years (70.3% retention rate in the cohort). Children living in neighborhoods with community cultural centers were protected from developing caries lesions in first molars (IRR 0.78, 95% CI 0.62-0.99); on the other hand, lower family income (IRR 1.34, 95% CI 1.03-1.76) and poor parents' perception of their children's oral health (IRR1.56, 95% CI, 1.18-2.06), were associated with an increased risk of caries. For the second article 4 dichotomy variables were constructed (caries experience, maternal schooling, family income and parents' perception on children oral health) to evaluate the caries predictive capacity in first permanent molars. Accuracy (using values of sensitivity, specificity, positive and negative predictive value) and efficiency (represented by the number-needed-to-treat - NNT) of these variables were also verified when used as indicators of the use of sealants. Caries experience, lower maternal schooling, lower family income and worse parents' perception about their children's health, assessed at baseline showed high accuracy to identify children who do not need the use of sealants; but failed to identify children who would benefit from such a strategy. In addition, when evaluating the number-needed-to-treat, all evaluated variables showed acceptable values (NNT≤ 11), considering that caries is a chronic and cumulative condition. In this sense, strategies that consider higher risk groups could be implemented in conjunction with broad strategies that consider the social determinants and common risk factors, thus promoting a greater reduction in the incidence of childhood caries.